Evaluation of the significance of mutation and expression of the specific chimeric oncogene Bcr-abl p210 in chronic myeloid leukemia in the Uzbek population - Makhmudova Mukhlisa Marif qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The use of tyrosine kinase inhibitors (TKI) considerably improved the prognosis for most patients with chronic myeloid leukemia (CML). However, the issue of resistance to TKI therapy remains a challenge. At present, much attention is paid to the study of molecular genetic profile of tumor cells in CML patients and the role of somatic mutations in various genes, beyond BCR-ABL1, in the development of resistance to TKI therapy. New data emerge on the frequency of somatic mutations in various genes by the time of primary diagnosis of CML, commonly in the chronic phase, and on clonal changes during treatment, also when the disease progresses. Of particular interest is the role of somatic gene mutations in the transformation of CML into accelerated phase and blast crisis. Special importance is attributed to the time between the detection of somatic mutations and the registration of disease progression. This review focuses on the results of recent and most relevant studies of molecular genetic profile of CML patients at various disease stages. These studies aim to reveal the associations between somatic mutations in genes and a response to TKI therapy, as well as to assess the prognostic value of the mutations detected upon primary diagnosis and CML therapy.